The Influence of Organizational Commitment and Work Engagement on Turnover Intention with Transformational Leadership as a Moderating Variable among Teachers at Mutiara Bunda Elementary School, Bandung - Sulaeman, Tina Emillia; Pratminingsih, Sri Astuti (Dinasti International Journal of Education Management and Social Science, 2025)
This study investigates the influence of organizational commitment (OC) and work engagement (WE) on turnover intention (TI), with transformational leadership (TL) as a moderating variable, among teachers at Sekolah Mutiara Bunda, Bandung. Employing a quantitative-verificative approach and survey method, data were collected from 98 respondents and analyzed using Moderated Multiple Regression (MMR). The first model indicated that both OC (β = –0.499, p < 0.001) and WE (β = –0.203, p = 0.048) significantly and negatively predicted TI, suggesting that higher levels of commitment and engagement reduce turnover intention. In the second model, the interaction effect between OC and TL was not statistically significant (β = –0.064, p = 0.376), indicating that TL does not moderate the relationship between OC and TI. Conversely, the interaction between WE and TL was significant (β = 0.222, p = 0.031), but in the opposite direction from the hypothesized model, suggesting that at high levels of TL, the negative impact of WE on TI weakens. The change in explained variance between models was modest (ΔR² = 0.022; p = 0.049), confirming the presence of a partial moderating effect. These findings emphasize the importance of strengthening organizational commitment and engagement to reduce turnover intention, while also reevaluating the contextual role of transformational leadership in retention strategies